2014
DOI: 10.1111/ecc.12181
|View full text |Cite
|
Sign up to set email alerts
|

Association between unmet needs and quality of life in hospitalised cancer patients no longer receiving anti-cancer treatment

Abstract: Assessing the quality of life and unmet needs of cancer patients is an integral part of palliative care. This cross-sectional study sought to determine whether there is an association between quality of life and unmet needs, anxiety and depression in cancer patients who are no longer receiving anti-cancer treatment. The sample consisted of 93 patients from the oncology department at the University Hospital in Ostrava for whom further cancer treatment had been terminated as ineffective in halting the progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 43 publications
(93 reference statements)
2
30
0
1
Order By: Relevance
“…Little attention has been paid to assessment of the impact of unmet needs on quality of life. 31 The present study showed lower quality of life in patients with more unmet needs in all domains with the exception of the domains chance to share emotions and religious needs. Bai and Lazenby 47 reported an association between quality of life and spiritual well-being of cancer patients.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Little attention has been paid to assessment of the impact of unmet needs on quality of life. 31 The present study showed lower quality of life in patients with more unmet needs in all domains with the exception of the domains chance to share emotions and religious needs. Bai and Lazenby 47 reported an association between quality of life and spiritual well-being of cancer patients.…”
Section: Discussionsupporting
confidence: 46%
“…[16][17][18][19] Health-related quality-of-life measures have been increasingly used to evaluate differences in quality of life based on the setting and type of care provided 20,21 and type of illness 22 as well as to determine factors that might influence the patients' quality of life. [23][24][25][26][27][28][29][30][31] Some studies showed associations between quality of life and sociodemographic characteristics of patients, 21 type of illness, 22 type of intervention, 23 physical symptom burden, [24][25][26][27] patients' functional status, 25 and unmet needs. [28][29][30][31] The Czech Ministry of Health funded a project supporting research into quality of life in palliative care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the relationship between unmet needs and quality of life (Bužgová et al . ) and between unmet needs and patient′s condition (Turner et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the delivery of PPC makes it easier for patients to stay in oncology care ward and provides them with greater psychological comfort. Studies conducted in Czech Republic and Australia also showed that psychological needs are among the most essential needs of patients with cancer (22,23). Accordingly, healthcare providers should pay special attention to cancer patients' psychological needs and provide them with appropriate PPC in order to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%